2003
DOI: 10.1034/j.1399-0004.2003.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Five new subjects with ring chromosome 22

Abstract: Ring chromosome 22, a rare cytogenetic finding, was first described by Weleber et al. in 1968. Since then approximately 50 patients have been reported in the medical literature. We describe five previously unreported subjects with ring chromosome 22 syndrome, summarize the clinical findings of reported patients from the literature and discuss the involvement of the ring chromosome and clinical outcome. Our subjects demonstrated the prominent features of this syndrome including mental retardation, hypotonia, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
14

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 26 publications
0
14
0
14
Order By: Relevance
“…К л и н и ч е с к и е н а б л ю д е н и я С подросткового возраста описаны расстройства на-строения [8,9].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
See 3 more Smart Citations
“…К л и н и ч е с к и е н а б л ю д е н и я С подросткового возраста описаны расстройства на-строения [8,9].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
“…У пациентов с аномалиями внутренних органов выявлена значительная протяженность мутации: по-мимо локуса 22q13 она захватывает проксимально рас-положенные гены, отвечающие за органогенез плода (22q12, 22q11) [8].…”
Section: Ch I Ld Neurology R U S S I a N J O U R N A L O Funclassified
See 2 more Smart Citations
“…havioral anomalies, microcephaly, hypotonia, and mild dysmorphic traits [Weleber et al, 1968;Ishmael et al, 2003]. Clinical features of r(22) overlap with those of 22q13 terminal deletion [Lam et al, 2006] and, in both syndromes, SHANK3 is suggested to be the most likely candidate gene for the neurobehavioral features [Luciani et al, 2003].…”
mentioning
confidence: 99%